Certain Criminalistic and Criminal Procedure Problems Arising in the Investigation of Criminal Cases Related to Organized Extortion as Exemplified by Kazakhstan and Kyrgyzstan - SMOILOV, Samat Zhumagalievich; TASTEKEYEV, Kayrat Kulbayevich; KALIAKPEROVA, Yelena Nikolaevna (Journal of Advanced Research in Law and Economics, 2016)
Article refers to the study of theoretical issues and problems arising in the investigation of criminal cases related to organized extortion as exemplified by Kazakhstan and Kyrgyzstan. The paper examines the theoretical and methodological ideas, solutions of the appropriate problems related to organized extortion, considers criminalistic aspects of the appropriate issues. The paper presents the basic concepts and categories, the structure and the system of investigating criminal cases related to organized extortion, as well as the genesis of the formation of a technique to investigate criminal cases concerning organized extortion, the concept of interrelation of the problematic issues related to the investigation of organized extortion criminal cases in the provisions of the Criminal Procedure Code of the states. The authors have made a legal analysis of the Criminal Procedure Code rules and regulations applicable in the investigation of organized extortion criminal cases, have studied the legal problems in application of new techniques in the investigation of such criminal cases. The basic theoretical principles and recommendations for the improvement of the existing criminal procedural legislation of the Republic of Kazakhstan and the Kyrgyz Republic have been sets out.